2012
DOI: 10.5714/cl.2012.13.2.088
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in ammonia gas sensing behavior by polypyrrole/multi-walled carbon nanotubes composites

Abstract: Polypyrrole (PPy)/multi-walled carbon nanotubes (MWCNTs) composites were prepared by in situ polymerization of pyrrole on the surface of MWCNTs templates to improve the ammonia gas sensing properties. PPy morphologies, formed on the surface of MWCNTs, were investigated by field emission scanning electron microscopy. The thermal stabilities of the PPy/MWCNTs composites were improved as the content of MWCNTs increased due to the higher thermal stability of the MWCNTs. PPy/MWCNTs composites showed synergistic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 35 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The immediately dangerous to life or health concentration (IDLH) towards NH 3 is 300 ppm [13][14][15][16]. When the human body is in the low concentration of NH 3 environment such as 35 ppm for a long time, it will also cause the increase of blood ammonia concentration, which will lead to a serious of pathological changes of organs such as liver and kidney [14,17,18]. Therefore, it is very important to develop a new NH 3 gas sensor with high response and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The immediately dangerous to life or health concentration (IDLH) towards NH 3 is 300 ppm [13][14][15][16]. When the human body is in the low concentration of NH 3 environment such as 35 ppm for a long time, it will also cause the increase of blood ammonia concentration, which will lead to a serious of pathological changes of organs such as liver and kidney [14,17,18]. Therefore, it is very important to develop a new NH 3 gas sensor with high response and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a polypyrrole carbon nanotube (PPy-CNTs) composite exhibits very different electronic properties compared to the sole composites of PPy and CNTs. Furthermore, composite films of CNTs with polypyrrole are well suited for gas sensor applications [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The composite was used to detect ammonia vapours in the concentration range of 1-30 ppm, and the maximum response was calculated to be 46.44% at 5 ppm. A PPy/MWCNTs nanocomposite was fabricated by Jang et al 39 using the in-situ polymerization method. They used this composite for sensing ammonia vapours at temperatures ranging from room temperature to 100°C and calculated the sensitivity to be 65%.…”
Section: Ammonia Vapour Sensingmentioning
confidence: 99%